Diagnostic Domain Defense: Autism Spectrum Disorder and the DSM-5. (7th February 2015) - Barker, Kristin; Galardi, Tasha R.
Abstract: A central mechanism by which medicalization occurs is through domain expansion, wherein an existing diagnostic definition widens to include cases beyond its original scope. This has been especially commonplace with respect to mental illness diagnoses. In contrast, there are few clear instances of domain contraction. The controversy surrounding the revisions to autism in advance of the publication of the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders ( DSM-5) is thus of considerable importance. Many autism advocates feared the new definition of autism would exclude a significant number of individuals who are already diagnosed. We examine lay claims making to this perceived instance of domain contraction through a content analysis of online reader comments to a high-profile New York Times article reporting on the DSM-5 autism criteria. Our analysis points to an amorphous group of social stakeholders who express a variety of concerns about unabated medicalization. We also identify the stance of diagnostic domain defense, which is an oppositional response by laypeople with a personal connection to a diagnosis to a real or perceived challenge to the definitional boundaries of that diagnosis. Our analysis explicates the dimensions of diagnostic domain defense, which include its grounding in experiential certainty and anguish, and the accrual and deployment of diagnostic resources. We make a case for the utility of this concept for theorizing the relationship between lay claims making, diagnoses, and medicalization. We also make a case for the use of online reader comments as a way to unobtrusively study lay claims making related to pressing social problems in the Internet era. Un mecanismo central a través del cuál se produce la medicalización es la ampliación del dominio, es decir cuando la definición de un diagnóstico se amplía para incluir casos más allá de su alcance original. Esto ha sido especialmente común con respecto a los diagnósticos sobre enfermedades mentales. Sin embargo, existen pocos casos de contracción del dominio, por ello es de mucha importancia la controversia en torno a las revisiones de autismo ante la publicación del DSM-5. Muchos defensores del autismo temían que la nueva definición excluiría un número significativo de personas que tienen el diagnóstico de autismo. A través de un análisis de contenido de 642 comentarios de lectores en línea sobre un artículo de alto perfíl del periódico New York Times sobre los criterios de autismo DSM-5 pudimos examinar la percepción del público sobre la contracción del dominio de autismo. En nuestro análisis encontramos que los actores sociales que expresan una variedad de preocupaciones sobre esta nueva medicalización constituyen un grupo amorfo. También encontramos que los actores que tienen una conexión personal con un diagnóstico de autismo se oponen a los límites reales o percibidos de la nueva definición de ese diagnóstico. El concepto de contracción de dominio sirve para teorizar sobre la relación entre reclamos, diagnósticos y procesos de medicalización o desmedicalización. Igualmente, el uso de los comentarios de los lectores en línea es una forma discreta para los sociólogos de estudiar los reclamos relacionados con problemas sociales urgentes en la era de Internet.